The night before Christmas - Moore, Clement Clarke, 1779-1863.; Malvern, Corinne, 1905-1956 (Golden Book, 2014)
The text of the famous Christmas poem is accompanied by pictures of a family as they might have appeared when the poem was written in 1822.
Keywords: Santa Claus -- Juvenile poetry; Christmas poetry; Children's poetry, American; Board books